2016
DOI: 10.5057/ijae.ijae-d-16-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Bio-signal Interactive Virtual Reality on Subjective Impression - A Preliminary Study

Abstract: Abstract:We developed a bio-signal interactive virtual reality (VR) system to investigate the impression of users as a pilot study. In this study, three different VR scenes were given to the subjects of 20 healthy university students: bonfire (regulated with Electrocardiogram), firefly and butterfly (regulated with respiration signal). The subjective outcomes were assessed using the visual analogue scale. For the purpose of comparison, each subject also experienced the same scenes regulated with sinewave and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Another study observed the entrainment of HR by sedative music in which the tempo gradually decreased [13]. As for the case of interaction of the heartbeat with other than music, one study reported that the heartbeat interactive virtual reality (VR) gave an impression to the participants as such the interactive VR contents seemed to be comfortable and natural [14].…”
Section: Introductionmentioning
confidence: 99%
“…Another study observed the entrainment of HR by sedative music in which the tempo gradually decreased [13]. As for the case of interaction of the heartbeat with other than music, one study reported that the heartbeat interactive virtual reality (VR) gave an impression to the participants as such the interactive VR contents seemed to be comfortable and natural [14].…”
Section: Introductionmentioning
confidence: 99%